Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper for the Republic of Korea focuses on the role of monetary policy in the current context of slowing growth and rising inflation pressures. Korea has not remained immune to the global slowdown, and with the cycle turning downward, the trade-off between inflation and growth is deteriorating. Subprime-related turbulences in financial markets add an extra element of uncertainty to the economic outlook, and have led to a noticeable increase in Korea's stock market and exchange rate volatility.